G‐Quadruplex‐Stimulated Optical and Electrocatalytic DNA Switches. Issue 30 (22nd April 2015) - Aizen, Ruth; Golub, Eyal; Trifonov, Alexander; Shimron, Simcha; Niazov‐Elkan, Angelica; Willner, Itamar
<x xml:space="preserve">Abstract</x> The K+/18‐crown‐6‐(or [2.2.2] cryptand)‐stimulated formation and dissociation of G‐quadruplex nanostructures lead to the cyclic and switchable photonic and electrocatalytic molecular devices.